2014
DOI: 10.1111/jace.13021
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Toughness of Plasma‐Sprayed Thermal Barrier Ceramics: Influence of Processing, Microstructure, and Thermal Aging

Abstract: Fracture toughness of thermal barrier coatings (TBCs) has gained significant interest in recent years as one of the dominant design parameters dictating selection of materials and assessing durability. Much progress has been made in characterizing and understanding fracture toughness of relevant TBC compositions in their bulk form, but it is also apparent that the toughness is significantly affected by process‐induced microstructural defects. In this investigation, a systematic study of the influence of coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 47 publications
7
72
0
Order By: Relevance
“…Firstly, a intervening bond‐coat is deposited on superalloy to facilitate strong adhesion between substrate and a top‐coat. Subsequently, the ceramic top‐coat is deposited to provide the thermal insulating function . A common material for the top‐coat is the yttria‐stabilized zirconia (YSZ), since it exhibits a low thermal conductivity [~2.5 W·(m·K) −1 ] and a high thermal expansion coefficient (~11 × 10 −6 K −1 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, a intervening bond‐coat is deposited on superalloy to facilitate strong adhesion between substrate and a top‐coat. Subsequently, the ceramic top‐coat is deposited to provide the thermal insulating function . A common material for the top‐coat is the yttria‐stabilized zirconia (YSZ), since it exhibits a low thermal conductivity [~2.5 W·(m·K) −1 ] and a high thermal expansion coefficient (~11 × 10 −6 K −1 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The fracture toughness of five YSZ coatings showed significant differences ranging from 1.11 to 1.17 MPa √ m. It was reported that the fracture toughness of APS YSZ coatings processed by indentation method is 1.35-3.30 MPa √ m [12,23]. The fracture toughness for YSZ coatings was reported to be much larger, probably due to the thinner coating thickness [23][24][25]. YSZ coatings average fracture toughness was 1.13 MPa √ m. And as shown in Table 2, there is an approximately 48% lower value compared to thick SiC fiber/YSZ composite coatings that had a average fracture toughness of 1.67 MPa √ m, because fiber-reinforced composites have a better fracture toughness [26].…”
Section: Analysis Of Fracture Toughness and Thermal Shockmentioning
confidence: 96%
“…The fracture toughness of five YSZ coatings showed significant differences ranging from 1.11 to 1.17 MPa √ m. It was reported that the fracture toughness of APS YSZ coatings processed by indentation method is 1.35-3.30 MPa √ m [12,23]. The fracture toughness for YSZ coatings was reported to be much larger, probably due to the thinner coating thickness [23][24][25].…”
Section: Analysis Of Fracture Toughness and Thermal Shockmentioning
confidence: 97%
“…It is thermodynamically compatible with the protective thermally grown oxide (TGO). It also exhibits high fracture toughness over 2 MPa.m 1/2 [11,12]. All these have made YSZ the preferred choice for top coat material in TBC applications for many decades.…”
Section: Top Coatmentioning
confidence: 99%